Bering Land Bridge National Preserve, Alaska : draft general management plan/environmental assessment, land protection plan, wilderness suitability review. - United States. National Park Service. Alaska Regional Office.; United States. National Park Service. (Anchorage, Alaska : U.S. Dept. of the Interior, National Park Service, Alaska Regional Office, 1985)
"March 1985"--Cover. Includes bibliographical references (p. 192-195). Mode of access: Internet.